Courtly etiquette and government in seventeenth century viceregal Peru - Gálvez Peña, Carlos M. (2024)
Published in Lima in 1644, fray Alonso de Almeida´s Pretendiente de la tierra is a complex treatise that explores both the nature of power and the mission of Christian government embodied by the Spanish Empire of the seventeenth century. It is an original appropriation of both Castiglione´s The Courtier (1528) and Botero´s Reason of State (1589). An interesting case of cultural appropriation, Almeida´s work is, however, notably original, since it is designed to be a manual for honorees of the Peruvian viceroyalty to navigate the court at Madrid. The book not only covers formalities and protocol, but, above all, delves into their meaning in the wider context of an ailing Hispanic Monarchy and the relaunch of government based on anti-Machiavellianism. Almeida’s notion of Christian government includes both the individual and the State.